Inovasi Metode Pembelajaran PAI Sebagai Upaya Meningkatkan Prestasi Belajar Siswa di Alkhairaat Labuha - Amanan Sulaiman (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2016)
Recognized  that  the implementation of  learning PAI. In many schools still meet obstacles, therefore the need for innovation method or way of learning, With the innovative method of learning expected of teachers is not as if a single source of information. Teachers are able to innovate in teaching methods open up horizons of  students to be innovative and creative. Through innovative  teaching methods, learning  atmosphere  in the classroom is not  stuck in an atmosphere of rigid and monotonous.  So that students can easily understand  the material presented.  Susana  will  make  student  learning unsaturated received materials  from the teacher.  Therefore, the authors are interested to study  " innovation Learning  Method PAI in Efforts to improve. Student Achievements in Labuha Alkahiraat Aliyah"